Coordination of construction behavior in the termite Procornitermes araujoi: structure is a stronger stimulus than volatile marking - Fouquet, D.; Costa-Leonardo, A. M. [UNESP]; Fournier, R.; Blanco, S.; Jost, C. (Springer, 2014)
We studied the behavioral coordination mechanisms underlying morphogenesis in shelter construction by the termite Procornitermes araujoi. We detected positive feedback in both digging and pellet deposition behavior. The literature suggests two stimuli for these positive feedbacks: the emerging structure itself or volatile chemical marking added to the construction material. The experiments showed that the most important stimulus is the change in structure, but indirect evidence suggests that there is also some chemical marking involved. Beyond shedding light on the behavioral mechanisms of termite shelter construction, these results also stress the necessity of direct experimental approaches in order to identify and properly weight different coordination mechanisms underlying morphogenesis in biological systems.
Keywords: Morphogenesis; Construction behavior; Stigmergy; Shelter construction